Supply-chain finance: An empirical evaluation of supplier outcomes - Niklas Amberg; Tor Jacobson; Yingjie Qi (Sveriges Riksbank, 2024)
Buyers and suppliers have diverging interests about trade-credit maturities: buyers desire long payment periods as a source of cheap funding, while suppliers prefer swift payments to avoid locking up scarce liquidity in idle assets. A fast-growing financial product innovation - supply-chain finance (SCF) - offers to resolve these diverging interests, but its net effect on suppliers is a priori unclear. We study the effects of SCF programs on suppliers using unique invoice-level data from a large Swedish bank. We find that SCF programs relax suppliers' liquidity constraints and thereby enable them to grow their sales, employment, and investments.
Keywords: G21; G32; D22; 330; Trade credit; supply-chain finance; reverse factoring; financial constraints